IGY: A new model for LGBTQ youth groups?. Issue 2 (3rd April 2017) - Brooks, Orren
ABSTRACT: This study explores the experiences of homosexual teenagers who are members of the Israeli lesbian, gay, bisexual, transgender, and queer youth organization called Israel Gay Youth. Through an interview-based study with members and counselors, this study reveals how although various therapeutic practices take place during the weekly meetings, all members seem to place an emphasis on Israel Gay Youth being a bona fide youth movement. Israel Gay Youth's adoption of the Israeli youth movement model allows members to position the organization and subsequently themselves, in a place of greater equality to the rest of society, thus shirking off any array of morbid associations related both to support groups and homosexual tendencies.